Pre- and In-Service Teachers’ Assessment and Feedback in EFL Writing: Changes and Challenges - Yunjun Kong; Edit Katalin Molnár; Nan Xu (SAGE Open, 2022)
In research on EFL writing, much attention has been paid to teachers’ practises in assessment or feedback, but little is known about teachers’ behaviors in these two domains as a whole. There also seems to be a paucity of research on how teachers’ reactions to student writing develop from pre- through in-service. The current study, using a cross-sectional method, aims to compare pre- and in-service teachers’ assessment and feedback in EFL writing pertinent to their potential changes and challenges in responding to student text. Three groups of participants (59 pre-practicum trainees, 31 post-practicum trainees, and 32 in-service teachers) in Mainland China were involved in a simulation task for assessing a descriptive text by using the given scoring rubrics and providing written feedback to the same text. The results of the assessment task showed that there is a salient change in the participants’ severity from pre- through in-service in assessing the student text; participants with less teaching experience focused on conceptual aspects of the text, whereas those with more experience highlighted linguistic issues in the assessment task; and some participants in each group had problems with proper use of the rating scales. Results of the feedback task revealed that all three cohorts at different professional development stages probably faced challenges in reacting to the text due to the limited quantity and poor quality of their written responses. These findings underscore the necessity for assessment literacy training for teachers in both pre-service and in-service programs.